Investigation on Customers’ Attitude towards Chatbots in Banking Industry of India - Gupta, Amisha; Sharma, Deepti (Recent Developments in Engineering Research Vol. 12, 2021)
The customer's attitude towards chatbots in the Indian banking industry is investigated in this study. The author conducted correlation analysis to determine and comprehend client attitudes on chatbot acceptability and usage in the banking business. The primary survey is used to collect data. 100 people were targeted, out of which 72 responded. The study concludes a positive correlation between the attitude and the adoption of chatbots. As part of the conclusion author made some suggestions and recommendations discussing the implementation of chatbots in the banking industry of India. It is very much possible with the advancement of technology and the upgrading of consumers knowledge more and more communication will occur with the help of chatbots. Henceforth banking companies should be ready for this shift.